Determining dose enhancement factors of high-Z nanoparticles from simulations where lateral secondary particle disequilibrium exists. (7th August 2019) - Rabus, Hans; Gargioni, Elisabetta; Li, Wei Bo; Nettelbeck, Heidi; Villagrasa, Carmen
Abstract: Nanoparticles (NPs) containing high atomic number (high- Z ) materials have been shown to enhance the radiobiological effectiveness of ionizing radiation. This effect is often attributed to an enhancement of the absorbed dose in the vicinity of the NPs, based on Monte Carlo simulations that show a significant local enhancement of the energy deposition on the microscopic scale. The results of such simulations may be significantly biased and lead to a severe overestimation of the dose enhancement if the condition of secondary particle equilibrium is not met in the simulation setup. This current work shows an approach to estimate a 'realistic' dose enhancement from the results of such biased simulations which is based on published photon interaction data and provides a way for correcting biased results.